Heat Recovery System with the Embedded Thermosiphon-Type Heat-Exchange Apparatus - Yefimov, Aleksandr Vyacheslavovich; Goncharenko, Aleksandr Leonidovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
It is proposed to use the heat-exchange apparatus whose surface was formed by two-phase siphons of a closed type for the system of deep recovery of the heat of escaping gases of the boiler with the steam capacity of 0.278 kg/s. To protect the gas escape channel from the damage the by-pass was arranged for the portion of combustion gases passing by the heat-exchange apparatus that allows us to raise the temperature of escaping gases above the dew-point temperature. Due to the fact that the heat-exchange apparatus uses the physical heat of gases and also the heat released during the condensation of water steam from the combustion products of natural gas its surface is subdivided in two stages that use different liquids as an intermediate heat carrier for the thermosiphons, in particular the stage without the steam condensation uses water and the stage with the steam condensation uses the water-ammonia mixture. This required some improvement of the known methods of heat calculation for the thermosiphon-type heat exchange apparatus. Computing studies were carried out using the software developed by the authors. The investigation allowed us to establish that in the case of maintenance of the fuel rate at a fixed level the heat recovery system allows us to provide the steam production at a capacity of 0.278 kg/s and also to additionally heat 0,5049 kg/s of the heating system water in the hot water supply system in the range of 10 °C to 65 °C and also to generate the condensate at a capacity of 0.0247 kg/s. The comparison of heat-exchange apparatuses of a thermosiphon type and coil type showed that their structures are comparable with regard to heat engineering and overall indicators.